Neural Basis for Dyslexia and Picture Naming Deficits - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Eight dyslexic subjects, aged 20 +/-0.9 years, university students who were impaired on measures of reading, spelling and naming speed, matched for age and general ability with 10 control subjects, were scanned using PET while reading words and naming pictures, in a study at the Institute of Psychiatry, University College, and the Institute of Neurology, London, UK.